1999
DOI: 10.1034/j.1399-3089.1999.00031.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of macrophage depletion on delayed xenograft rejection: studies in the guinea pig‐to‐C6‐deficient rat heart transplantation model

Abstract: The purpose of this study was to investigate the effect of macrophage depletion, using liposome-encapsulated dichloromethylene diphosphonate (Lip-Cl2MDP), on delayed xenograft rejection (DXR) in the guinea pig-to-C6-deficient rat heart transplantation model. In this model, hyperacute rejection does not occur, but, in untreated recipients, xenografts are still destroyed by DXR within 1-2 days. Graft survival was 68 +/- 8.4 h in splenectomized control rats, 77 +/- 16.3 h with Lip-Cl2MDP alone, 99 +/- 10.4 h with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
11
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 26 publications
2
11
0
Order By: Relevance
“…Thus, the development of strategies for specifically suppressing xenogeneic cell-triggered macrophage activation may be essential to the maintenance of durably functional cellular xenografts, and may also be beneficial in solid organ xenotransplantation for which macrophages have also been implicated in rejection. 23,24 SIRP␣ is an ITIM-bearing inhibitory receptor expressed on macrophages that plays an important role in controlling macrophage activation. 12,13 It has been demonstrated that SIRP␣ on macrophages recognizes CD47 as a marker of "self" and that CD47-SIRP␣ signaling prevents autologous phagocytosis of normal cells.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the development of strategies for specifically suppressing xenogeneic cell-triggered macrophage activation may be essential to the maintenance of durably functional cellular xenografts, and may also be beneficial in solid organ xenotransplantation for which macrophages have also been implicated in rejection. 23,24 SIRP␣ is an ITIM-bearing inhibitory receptor expressed on macrophages that plays an important role in controlling macrophage activation. 12,13 It has been demonstrated that SIRP␣ on macrophages recognizes CD47 as a marker of "self" and that CD47-SIRP␣ signaling prevents autologous phagocytosis of normal cells.…”
Section: Discussionmentioning
confidence: 99%
“…Macrophages have been proposed as one of the major effector cells responsible for CD4 ϩ T cell-mediated xenograft destruction. Unlike allografts in which the predominant cells seen are T cells, in rejecting xenografts the predominant cell is the macrophage (18,(23)(24)(25). The preponderance of macrophages in rejecting xenografts has led us and others to propose that these cells are primarily responsible for graft destruction (11)(12)(13)17).…”
Section: Discussionmentioning
confidence: 99%
“…The problem with these studies is that the evidence supporting the important role for macrophages was indirect. Temporary depletion of macrophages in nonobese diabetic (NOD) mice and diabetic C57BL/6 mice by liposome-encapsulated dichloromethylene diphosphonate (Lip-Cl2 MDP) caused a delay in xenograft rejection as well as a marked delay in the cellular infiltration by macrophages and T cells (12,18), supporting a major role for macrophages in xenograft rejection. However, the characteristics of this important macrophage-mediated response remain unclear.…”
mentioning
confidence: 99%
“…Only little is known about the mechanism and immunosuppressive require- Complement C6-deficient PVG (C-) recipients, unable to construct the terminal MAC (C5b-429) of the complement cascade due to an isolated genetic deficiency in C6 [42], reject discordant GP cardiac xenografts in an accelerated acute fashion within 1-2 days [3, 13, 21,22,44,45]. The C6 deficiency blocks a late step in complement activation of the classic and alternative complement pathway.…”
Section: Discussionmentioning
confidence: 99%